Disparity Between Cognitive Understanding and The Implementation of Pancasila Values Among Fifth Grade Students - Cela Talita Sianturi; Feby Fransiska Siregar; Riandita Kd. Pasaribu; Roseska Natalia Marito Simanjuntak; Siti Apriyanti Majid; Tohap Panuturi Sihombing (Jurnal Pendidikan Vokasi Indonesia, 2026)
This study was conducted to gain a deeper and more realistic understanding of how fifth-grade students at SDN 066053 comprehend Pancasila learning and how far they are able to apply its values in their daily lives. In practice, learning Pancasila is often limited to memorizing concepts, even though its main purpose is to shape students’ attitudes, habits, and character. Therefore, it becomes important to look not only at students’ knowledge, but also at how they behave in real-life situations. This research used a descriptive quantitative approach by distributing a questionnaire to 20 students. The instrument consisted of 10 statements that were designed to explore students’ understanding, attitudes, and daily behavior related to Pancasila values. The data collected were then analyzed using percentage calculations so that the results could be presented in a simple and easy-to-understand way, while still reflecting the actual condition in the classroom. The results show that most students already have a fairly good understanding of Pancasila learning. However, when it comes to applying these values in everyday situations, some students are still inconsistent. This indicates that understanding alone is not enough, and students need more guidance, examples, and practice so that these values can truly become part of their daily behavior.